THE PSYCHOLOGICAL STRUGGLE OF THE MAIN CHARACTER IN ERNEST HEMINGWAY’S “THE OLD MAN AND THE SEA” - Berdiyev Oston Maxmud o‘g‘li (TADQIQOTLAR, 2025)
Annotation. This article provides a comprehensive analysis of the psychological struggle of Santiago, the main character in Ernest Hemingway’s novella “The Old Man and the Sea”. Using a qualitative and descriptive methodology, the study examines Santiago’s emotional strength, inner dialogue, symbolic battle with the marlin, and the philosophical message of perseverance. The findings demonstrate that Hemingway constructs Santiago as a universal image of human dignity, moral courage, and spiritual endurance, proving that victory is not measured by material gain but by inner resilience.